Efektivitas Pengembangan E-LKPD Berbantuan Aplikasi Thunkable Berbasis Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Romadhon Hafild, M. Nazali; Putri, Tiya Permana; Damayanti, Frianka Ivana; Sari, Emilia; Rohman, Fatkhur; Pramudiyanti, Pramudiyanti (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Changes in the pattern of education in the 21st century force education units to change their learning strategies to answer the challenges of learning in the 21st century. Thinking skills that require high-order thinking skills are absolutely necessary. One of the high-level thinking skills that need to be improved is creative thinking ability. The ability to think creatively which has four indicators namely the ability to think smoothly, the ability to think original, the ability to think flexibly and the ability to think in detail is believed to help students to be better prepared to face changes in the challenges of the 21st century. One way to improve students' creative thinking skills is to use E-LKPD assisted by discovery learning-based thunkable application. The purpose of this study was to determine the effectiveness of E-LKPD development assisted by discovery learning-based thunkable application in IPAS subjects to improve students' creative thinking skills. The research subjects were fifth grade students of SDN 4 Talang Bandar Lampung. From the results of the effectiveness test conducted, it was found that the E-LKPD assisted by the discovery learning-based thunkable application in the IPAS subject was effective for use in improving students' creative thinking skills.